Tax policy transformation in Georgia: Assessing the effectiveness of general state tax amendments on economic sustainability and business growth (2017-2021) - Lezhava, Mamuka; Todua, Nugzar; Chikviladze, Mikheil; Shengelia, Lolita (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This research aims to determine the role of 2017-2021 general state tax amendments in terms of economic development and improvement of the business environment in Georgia. The following factors were used To evaluate the effectiveness of the tax burden: How the tax system is adjusted to the payer, whether it contributes to economic progress, and what the scope of taxes is. Tax policy experts were interviewed and asked to discuss tax policy reform objectives, options, and mechanisms. The interviews were semi-structured, supported by a briefing document and a topical guide, audio-recorded, transcribed, and analyzed. The efficiency of implemented changes for the EU Association Agreement was also evaluated. Compared to Georgian tax policy, EU tax policy is more liberal. The research revealed opportunities, future perspectives, and the significance of tax reforms and their positive effect on businesses. Based on in-depth interview findings, a detailed analysis of the financial sector is offered.